The organic matter content and pH of forest soils in the Brodnica Forest Division - Załuszniewska, Aleksandra; Bieniek, Arkadiusz; Nogalska, Anna (Polish Journal of Agronomy, 2020)
The study was conducted in the Górzno and Czarny Bryńsk Forest, ranges which belong to the Brodnica Forest Dis-trict. Brunic Arenosol (Dystric) soils predominate in the Brodnica Forest Division (over 77% of the total area). The aim of this study was to analyze the granulometric composition, the organic matter content and pH values in H2O and KCl at three genetic horizons of soils (A – humus, B – sideric and C – parent material) within the crown extension of four tree species: English oak, European beech, Scots pine and Norway spruce. Silt and clay had a signifi-cantly higher share of A-horizon compared with B and C hori-zons. Soil samples collected under the crowns of Norway spruces were characterized by a significantly higher percentage of sand and a significantly lower percentage of silt than soil samples col-lected under beech and pine trees. In the analyzed soil horizons, pH values increased significantly with depth regardless of tree species. Tree species had a significant effect on the pH of the analyzed soils and the organic matter content of A horizon. Soil samples collected under the crowns of Norway spruces had sig-nificantly lower pH values than those collected under pine trees. Soil samples collected under the crowns of Norway spruces had significantly higher organic matter content than those collected under oak trees. There was a very high negative correlation be-tween organic matter content and the values of pH measured in 1 M KCl, and a high negative correlation between organic matter content and the values of pH measured in H2O suspension.